Report on business attachment with India International Insurance. - Chew, Ian Yen. (2009)
The report briefly touches on the attachment programme India International Insurance (I.I.I. for short) offers to me as a trainee. To say that this report wholly describes the benefits absorbed is a gross injustice to the company, who had put me through trainings in two departments, and what they had taught me during this period of ten weeks could not be contained in mere 1500 words.